Georgia State University Perimeter College LSAMP Transfer Bridge Program: A Path Forward for Broadening Participation in Stem - Birkes, Angela Y.; DeMeester, Karen M.; Major, Margaret H.; Simmons, Brian W. (Frontiers in Education, 2021)
Summer Bridge Programs are increasingly becoming a popular strategy for colleges and universities to retain more underrepresented minority students in science, technology, engineering, and mathematics (STEM) disciplines. Retaining students in STEM disciplines is a necessary first step in order to accomplish the ultimate goal of diversifying the STEM workforce to create innovative solutions for today’s complex problems. In this paper, the authors describe an exploratory and descriptive study of the promising Georgia State University Perimeter College (GSU-PC) Louis Stokes Alliance for Minority Participation (LSAMP) Transfer Bridge Program. Most summer bridge programs are designed to facilitate seamless entry into college for incoming first year students, but the GSU-PC LSAMP Transfer Bridge program is designed to support the successful transition of underrepresented STEM students transferring from a two-year to a four-year institution. Early results demonstrate that the Transfer Bridge participants were significantly more likely to enroll in a four-year STEM program, receive a STEM bachelor’s degree, enroll in a post-baccalaureate STEM program, and receive a STEM post-baccalaureate degree than a comparison group of non-Transfer Bridge students at Georgia State University Perimeter College.